2004
DOI: 10.1093/humrep/deh309
|View full text |Cite
|
Sign up to set email alerts
|

Risk of uterine leiomyomata in relation to tobacco, alcohol and caffeine consumption in the Black Women's Health Study

Abstract: BACKGROUND: Tobacco, alcohol and caffeine consumption may influence risk of uterine leiomyomata via changes in ovarian function or hormone metabolism. METHODS: We prospectively assessed the relation of these exposures to risk of self-reported uterine leiomyomata in the Black Women's Health Study. From 1997 to 2001, we followed 21 885 premenopausal women with intact uteri and no prior myoma diagnosis. Cox regression models were used to estimate incidence rate ratios (IRRs) and 95% confidence intervals (CIs). RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
3
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 48 publications
7
98
3
5
Order By: Relevance
“…Certain studies have shown that the incidence of hysteromyoma varies among populations of different ethnicities (11)(12)(13)(14)(15)(16). For example, the incidence of hysteromyoma in African females is three times as high as that in Caucasian females (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies have shown that the incidence of hysteromyoma varies among populations of different ethnicities (11)(12)(13)(14)(15)(16). For example, the incidence of hysteromyoma in African females is three times as high as that in Caucasian females (13).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of hysteromyoma in females of African descent is higher than in individuals of other ethnicities, including Hispanic and Asian individuals (11,15,16). Certain studies have indicated that other risks, such as family history, smoking, drinking, hypertension and weight increase, can increase the risk of hysteromyoma, in addition to the risk associated with ethnicity (12,14,16,17). A study by Mäkinen et al (8) indicated that 70% of patients with hysteromyoma in the Finnish population presented with a mutation in the second exon of MED12, which affected the genetically-conserved sequence of the MED12 protein.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a lack of control for smoking would not have explained the positive findings because, in medical literature, maternal smoking has either been inversely (Baron, 1996;Wolf et al, 2004;Templeman et al, 2008) or unassociated (Marshall et al 1998;Wise et al 2004) with the risk of fibroids, and positively associated with the risk of LBW and preterm birth (Horta et al, 1997;Chiolero et al, 2005). However, a lack of control for maternal body mass index, nutritional status and alcohol consumption might be a concern because they are positively Continued associated with both uterine leiomyoma (Wise et al, 2004;Terry et al, 2007) and adverse birth outcomes (Lim et al, 2007;O'Leary et al, 2009). Our study is prominent in utilizing an extensive and unselected nationwide population-based study to assess the risks of adverse pregnancy outcomes among women diagnosed with uterine leiomyoma.…”
Section: Discussionmentioning
confidence: 99%
“…The data are conflicting, with a RR of 1.6 for greater than one pack per day [2] to a decrease in risk (RR 0.7) [19,24]. In the well done Black Women's Health Study following almost 22,000 women there was no change in risk associated with tobacco smoking [30].…”
Section: Smoking Alcohol and Caffeinementioning
confidence: 99%